Description of Protosticta samtsensis sp. nov. (Odonata: Zygoptera: Platystictidae) from Samtse district, Bhutan - Gurung, Mer Man; Phan, Quoc Toan (Zootaxa, 2023)
Protosticta samtsensis sp. nov. (holotype ♂: Bhutan, Samtse District, Norgaygang gewog (Bara), 27.142670°N, 88.835228°E; altitude 1,264 m, 12-viii-2022), is described from a holotype male and a female paratype and compared with P. himalaica Laidlaw, 1917.